Tinjauan Literatur: Pelapukan dan Pengaruhnya terhadap Kekuatan Batuan - Dwi Yolanda Sumbung; S. Koesnaryo; Eddy Winarno; Singgih Saptono; Tedy Agung Cahyadi (Retii, 2020)
Rock strength can be known from it's physical and mechanical properties which are strongly influenced by weathering. It requires a lot of time and research cost to find out about the effect of weathering on rock strength in various types of rock, therefore research was conducted in a literature review. The higher of weathering class affect the decrease of rock strength.